2000
DOI: 10.1051/vetres:2000113
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines and viral respiratory disease in pigs

Abstract: -Swine influenza virus (SIV), porcine respiratory coronavirus (PRCV) and porcine reproductive and respiratory syndrome virus (PRRSV) are enzootic viruses causing pulmonary infections in pigs. The first part of this review concentrates on known clinical and pathogenetic features of these infections. SIV is a primary respiratory pathogen; PRCV and PRRSV, on the contrary, tend to cause subclinical infections if uncomplicated but they appear to be important contributors to multifactorial respiratory diseases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 124 publications
(161 reference statements)
7
129
0
Order By: Relevance
“…Exposure of porcine alveolar macrophages to LPS induces rapid and prolonged production of this chemokine, however, low levels of the proinflammatory cytokine, TNF, are also required [79]. A number of bacteria have been shown to induce CXCL8 production in host species including Mycoplasma hyopneumoniae, M. haemolytica, A. pleuropneumoniae, and swine influenza virus [1,16,126,131,132]. In addition, LPS is a potent inducer of 474 E.L. Thacker CXCL8 [63].…”
Section: Chemokinesmentioning
confidence: 99%
“…Exposure of porcine alveolar macrophages to LPS induces rapid and prolonged production of this chemokine, however, low levels of the proinflammatory cytokine, TNF, are also required [79]. A number of bacteria have been shown to induce CXCL8 production in host species including Mycoplasma hyopneumoniae, M. haemolytica, A. pleuropneumoniae, and swine influenza virus [1,16,126,131,132]. In addition, LPS is a potent inducer of 474 E.L. Thacker CXCL8 [63].…”
Section: Chemokinesmentioning
confidence: 99%
“…It has been demonstrated that cytokines, such as tumour necrosis factoralpha (TNF-a) [18], interferon-alpha (IFN-a) [28], interleukin (IL)-1 [6,11] and interleukin-10 [12,33] can induce apoptosis. A PRRSV infection generally fails to induce substantial amounts of IFN-a [1,30,32]. This argues against a possible role of this cytokine in PRRSV-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…This argues against a possible role of this cytokine in PRRSV-induced apoptosis. IL-1, however, is produced at high levels in the lungs of PRRSV-infected pigs from 3 till 10 days after inoculation [31] and a weak TNF-a production has been demonstrated at 12 and 13 days after inoculation [32]. Furthermore, the induction of IL-10 mRNA in alveolar macrophages has been reported in PRRSV-infected pigs [29].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison swine influenza (SIV)-specific T cells are detected within 7 dpi (31). Although SIV induces a significant inflammatory response in the respiratory tract that appears related to viral clearance (32), no such inflammation is associated with PRRS (32,33). Despite a delay in virus-specific T cell responses, Ab responses to PRRSV of all major isotypes occur 6 -14 dpi in blood or BAL (34 -36).…”
mentioning
confidence: 99%